The attitudes of academics at the State University of Maringa regarding sport at 3 Grade: a longitudinal study - Juarez Vieira do Nascimento; Celso Souza; Christi Noriko Sonoo; Shizue Mizuta (Journal of Physical Education (Maringá), 2008)
This study aims at observing the undergraduate student throughout the period needed to satisfy the curricular demands in Physical Education and analysing his attitude towards it. It was necessary to identify the reasons for his choice of modality verifying the degree of attitude and its changes during the semesters attended in the subject. Population was formed by all freshmen enrolled in the 2nd semester of 1987 and in the 1st semester of 1988. The sample consisted of 141 students for the 2nd semester of 198 7 and 24 7 for the 1st semester of 1988. The student became a participant in the study on answering a questionnaire continually or intermitently for at least three semesters. As means of measuring, an option was made for questionnaire adapted from studies by SOUZA (1983). The questionnaire of Likert type, termed TAPRADES, with reliable coefficient of 0,87 made the analysis of attitude possible. The results showed that the majority of students tend to enroll themselves in their favourite modality in an available time. Most students opt for a modality and carry it on until they have fulfilled the curricular needs. Changes in modality take place more frequently during the 2nd semester. As for the number of semesters, the majority chose between 3 to 4 semesters for the duration of Physical Education, which seems to prevail. In relation to the subject's compulsoriness, the favorable opinions decreased as semesters went by whereas unfavorable opinions increased gradually. The students' attitude, in general, was positive in most courses of the Institution, where social and physical aspects contributed significantly to this result while in the congnitive aspect they showed some indifference. Thus, we assume that the students believe that the syllabus helps physical and social development. About half the students did not alter their attitude concerning the subject duríng the period this study was carried out. Those who changed attitudes, did it for better.